(untitled) (Scientific Journal of Research Studies in Future Civil Engineering, 2025)
This study presents a comprehensive computational assessment of yield line mechanisms in steel–concrete composite slabs by incorporating real material nonlinearities derived from verified experimental data. The research integrates finite element analysis (FEA) with experimental datasets from large-scale composite slab tests to accurately predict the formation, orientation, and progression of yield lines under various load conditions. A nonlinear constitutive model is employed to capture the stress–strain behavior of both steel and concrete, reflecting their realistic tension stiffening, compression softening, and strain-hardening characteristics. The computational model was validated against experimental bending tests on composite slabs with different shear span-to-depth ratios and boundary conditions. Results reveal that the inclusion of real material nonlinearities significantly improves the correlation between theoretical yield line predictions and experimental ultimate load capacities. Moreover, yield line patterns obtained from the simulations display closer conformity to observed crack propagation and ultimate failure modes, compared to classical linear assumptions. The study further establishes empirical relations linking material parameters—such as concrete compressive strength and steel yield stress—to yield line geometry and failure energy. The findings contribute to the refinement of current analytical design methods, offering a more realistic predictive framework for the ultimate capacity and post-yield behavior of steel–concrete composite slabs.